On Behalf of Holy Creatures: Hélène Cixous Reads Leviticus, or, la lecture immonde - Klangwisan, Yael (Relegere, 2018)
This article performs a critical creative reading of several texts: Lev 11, Lispector’s The Passion according to G. H., and Cixous’s essay "The School of Roots". Each of these texts seeks to understand the human relation to the animal. Cixous’s project in "The School of Roots" is, as Derrida does in L’animal, to interrogate and reinscribe the biblical text, so that another relation between the human and the animal might become possible. From the platform that Lispector and Cixous create, this reader seeks to open the biblical text to a counter-reading on behalf of the holy creature.